Gaining future competitive advantage through corporate foresight value creation: A case study on local affiliate companies in ASEAN's automotive industry - Jaka Purwanto; Reza Ashari Nasution; Yudo Anggoro (Cogent Business & Management, 2023)
Local affiliate companies (LACs) in the ASEAN automotive industry play an important role in corporate foresight implementation by collaborating with the principal company (PC) who deal with the local market. As the movements in the local environment become more dynamic and complex, and competition becomes more intense, the role of LACs becomes more demanding. Hence, it is essential to understand value creation in LACs, especially because literature on this topic is still lacking. This study aims to explore the value created from the practice of corporate foresight in automotive LACs. A qualitative method was employed, which consisted of in-depth, semi-structured interviews with 27 respondents. Eight LAC cases were selected based on their functional availability, accessibility, and acceptance. The results show that corporate foresight positively affects organisational learning, agility, and ambidexterity capability. In addition, organizational learning capability plays an important role to amplify its value creation. As such, this study provides insight into the mechanism through which organisational values are created and organisational capability influences competitive advantage. The findings can enable decision-makers and practitioners to consider the best corporate foresight approach to implement for optimum value creation. This study's novelty lies in our theoretical framework hypothesis of corporate foresight value creation.
Keywords: 650; automotive industry; competitive advantage; corporate foresight; local affiliate company; value creation